A method for preparing a 3D printing mortar

CN123003198APending Publication Date: 2026-10-30HANGZHOU ZHUBANG ENGINEERING TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611206267.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-10
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0006]针对现有技术的不足,本发明提供了一种3D打印砂浆制备方法,解决了粉体物料遇水发生团聚结块造成砂浆流变性能波动、促凝材料与水泥成分过早接触发生凝结反应造成打印设备堵塞、干燥的建筑垃圾破碎筛分料吸收水分引发砂浆流动度丧失,以及高转速搅拌硬质骨料破坏浆体结构并产生设备磨损的问题

Benefits of technology

[0022]1、本发明通过将第一部分拌合水与聚羧酸减水剂和六偏磷酸钠混合得到活性分散液,再将预混干粉匀速倒入活性分散液中得到初级浆体,防止粉体物料直接加水产生团聚结块,保障快硬水泥、纤维和钠基膨润土在浆体内部均匀分散,提供稳定的砂浆流变状态。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123003198A_ABST
    Figure CN123003198A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of building 3D printing materials, and discloses a 3D printing mortar preparation method, which comprises the following steps: mixing mineral powder, fly ash, fluorogypsum, quick-hardening cement, fibers, sodium gluconate, borax decahydrate and sodium bentonite to obtain premixed dry powder; mixing a first part of mixing water, polycarboxylic acid water reducing agent and sodium hexametaphosphate to obtain an active dispersion liquid; pouring the premixed dry powder into the active dispersion liquid to stir to obtain a primary slurry; dissolving liquid sodium silicate in a second part of mixing water to obtain a sodium silicate supplement liquid; reducing the rotating speed, synchronously adding dry building waste crushing and screening material and the sodium silicate supplement liquid into the primary slurry to stir to obtain 3D printing mortar. Through step-by-step slurry preparation and synchronous feeding, the application prevents powder agglomeration and caking, delays the setting reaction, uses the dry building waste crushing and screening material to absorb moisture and form a gel layer on the surface, guarantees continuous extrusion and stacking forming of the mortar, and reduces the equipment wear and tear by reducing the rotating speed to avoid damaging the slurry structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of 3D printing materials technology for buildings, specifically a method for preparing 3D printing mortar. Background Technology

[0002] Preparing 3D printing mortar from crushed and screened construction waste requires balancing the continuous extrusion time of the mortar within the printing equipment with the layer-by-layer stacking support capacity after extrusion. Existing preparation processes directly mix powder materials with water, which easily leads to powder agglomeration and clumping upon contact with water, affecting the uniformity of powder dispersion within the mortar and causing fluctuations in the rheological properties of the mortar system.

[0003] To meet the rapid setting requirements of 3D printing, accelerators are added during the mixing stage. However, these accelerators react prematurely with the cement components, shortening the mortar's working time and causing blockages in the printing equipment's pipes. Furthermore, the varying porosity of dried construction waste crushed and screened material leads to fluctuations in water absorption. Directly mixing this dried material into the mortar causes it to rapidly absorb moisture, resulting in a loss of mortar fluidity.

[0004] Maintaining high-speed mixing during the mixing stage of hard construction waste aggregates can cause shear forces that disrupt the early-formed slurry structure. At the same time, the hard aggregates can cause mechanical wear on the internal components of the mixing equipment, increasing the operating and maintenance costs of the equipment.

[0005] Therefore, it is necessary to provide a method for preparing 3D printing mortar to solve at least one of the above-mentioned technical problems. Summary of the Invention

[0006] To address the shortcomings of existing technologies, this invention provides a method for preparing 3D printing mortar, which solves the problems of mortar rheological properties fluctuation caused by the agglomeration and clumping of powder materials when exposed to water, clogging of printing equipment caused by premature contact between accelerators and cement components, loss of mortar fluidity caused by the absorption of moisture by dry construction waste crushed and screened materials, and damage to the slurry structure and equipment wear caused by high-speed stirring of hard aggregates.

[0007] To achieve the above objectives, the present invention provides the following technical solution:

[0008] This invention provides a method for preparing 3D printing mortar, comprising the following steps:

[0009] Mineral powder, fly ash, fluorogypsum, rapid-hardening cement, fiber, sodium gluconate, borax decahydrate, and sodium bentonite are added to a dry powder mixer and mixed by controlling the speed of the dry powder mixer to obtain premixed dry powder.

[0010] The first batch of mixing water is injected into the planetary mortar mixer. Polycarboxylate superplasticizer and sodium hexametaphosphate are added to the first batch of mixing water. The speed of the planetary mortar mixer is controlled to stir, and an active dispersion is obtained.

[0011] Maintain the rotation speed of the planetary mortar mixer, pour the premixed dry powder into the active dispersion at a uniform speed, and continue stirring to obtain the primary slurry;

[0012] The liquid sodium silicate is completely dissolved in the second batch of mixing water to obtain the sodium silicate replenishment solution;

[0013] Reduce the speed of the planetary mortar mixer, and add the dry crushed and screened construction waste and sodium silicate replenishment solution to the primary slurry at the same speed. Maintain the speed of the planetary mortar mixer to obtain 3D printing mortar.

[0014] The weight parts of each raw material added to the dry powder mixer are as follows: 45-65 parts mineral powder, 15-20 parts fly ash, 15-28 parts fluorogypsum, 3-12 parts rapid-hardening cement, 0.03-0.12 parts fiber, 0.02-0.08 parts sodium gluconate, 0.02-0.05 parts borax decahydrate, and 0.5-1.5 parts sodium bentonite.

[0015] The weight proportions of each raw material added to the planetary mortar mixer are as follows: 9.9-18.2 parts of mixing water in the first part, 0.10-0.35 parts of polycarboxylate superplasticizer, 0.05-0.15 parts of sodium hexametaphosphate, 0.05-0.10 parts of liquid sodium silicate by dry weight, 8.1-9.8 parts of mixing water in the second part, and 80-120 parts of dried crushed and screened construction waste.

[0016] The specific operating conditions for controlling the speed of the dry powder mixer are as follows: control the speed of the dry powder mixer to 40-60 rpm and the mixing time to 1-2 minutes.

[0017] The specific operating conditions for controlling the speed of the planetary mortar mixer are as follows: control the speed of the planetary mortar mixer to 100-150 rpm and the mixing time to 30-60 seconds.

[0018] After the premixed dry powder is poured in, the operating conditions for continuous stirring are: maintain the planetary mortar mixer speed at 100-150 rpm and the continuous stirring time at 1-2 minutes.

[0019] Reduce the speed of the planetary mortar mixer, and simultaneously and uniformly add the dry crushed and screened construction waste material and sodium silicate supplementary solution to the primary slurry. The specific operating conditions for maintaining the speed of the planetary mortar mixer are as follows: reduce the speed of the planetary mortar mixer to 30-50 rpm, and after the dry crushed and screened construction waste material and sodium silicate supplementary solution are added, maintain the speed of the planetary mortar mixer at 30-50 rpm for 2-3 minutes.

[0020] Polycarboxylate superplasticizer and sodium hexametaphosphate are pre-dispersed in the first batch of mixing water to obtain an active dispersion. Premixed dry powder is added to the active dispersion and mixed to obtain a primary slurry. Liquid sodium silicate is completely dissolved in the second batch of mixing water to obtain a sodium silicate supplement, which isolates the liquid sodium silicate from the rapid-hardening cement in the premixed dry powder. Dry crushed and screened construction waste is added to the primary slurry simultaneously and at a uniform rate with the sodium silicate supplement, absorbing moisture from the supplement. The speed of the planetary mortar mixer is reduced to avoid damaging the primary slurry structure and to reduce wear on the planetary mortar mixer from the dry crushed and screened construction waste. The liquid sodium silicate mixes with the primary slurry to form a gel, creating a coating layer on the surface of the dry crushed and screened construction waste, providing support for continuous extrusion and layer-by-layer stacking of the 3D printing mortar.

[0021] This invention provides a method for preparing 3D printing mortar, which has the following beneficial effects:

[0022] 1. This invention obtains an active dispersion by mixing the first part of the mixing water with polycarboxylate superplasticizer and sodium hexametaphosphate, and then uniformly pouring the premixed dry powder into the active dispersion to obtain a primary slurry. This prevents the powder material from agglomerating and clumping when water is added directly, ensuring that the fast-hardening cement, fiber and sodium bentonite are uniformly dispersed in the slurry, and providing a stable mortar rheological state.

[0023] 2. This invention obtains sodium silicate replenishment solution by completely dissolving liquid sodium silicate in the second part of the mixing water, and simultaneously and uniformly adding dry construction waste crushed and screened material and sodium silicate replenishment solution to the primary slurry, thereby delaying the time for the liquid sodium silicate to react with the fast-setting cement and undergo rapid setting reaction. The dry construction waste crushed and screened material absorbs water, causing the liquid sodium silicate to react on the surface of the dry construction waste crushed and screened material to form a gel layer, ensuring continuous extrusion and stacking of 3D printing mortar.

[0024] 3. This invention reduces the speed of the planetary mortar mixer when adding dried construction waste crushed and screened material and sodium silicate replenishment solution, thereby avoiding the high shear force generated by high speed that damages the primary slurry structure. At the same time, it reduces the physical wear of the planetary mortar mixer on the dried construction waste crushed and screened material during the mixing process, thus reducing the equipment operation and maintenance costs. Attached Figure Description

[0025] Figure 1 The X-ray diffraction patterns of samples at different stages in Example 1 of the present invention are shown.

[0026] Figure 2 The Fourier transform infrared spectra of samples at different stages in Embodiment 1 of the present invention are shown.

[0027] Figure 3The images show the evolution of ultrasonic pulse velocity in Embodiment 1 and Comparative Example 4 of the present invention.

[0028] Figure 4 The images show the lateral relaxation time distribution of Embodiment 1 and Comparative Example 5 of the present invention.

[0029] Figure 5 These are uniaxial compressive stress-strain diagrams for Embodiment 1 and Comparative Example 5 of the present invention. Detailed Implementation

[0030] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0031] Examples 1-3:

[0032] Example 1:

[0033] This embodiment provides a method for preparing 3D printing mortar, including the following steps:

[0034] Add 55kg of mineral powder, 20kg of fly ash, 20kg of fluorogypsum, 5kg of rapid-hardening cement, 0.07kg of fiber, 0.05kg of sodium gluconate, 0.03kg of borax decahydrate and 1.0kg of sodium bentonite into a dry powder mixer, control the dry powder mixer to mix, control the dry powder mixer speed to 50rpm and mix for 1.5min to obtain premixed dry powder;

[0035] 13.8 kg of the first batch of mixing water was injected into the planetary mortar mixer. 0.20 kg of polycarboxylate superplasticizer and 0.10 kg of sodium hexametaphosphate were added to the first batch of mixing water. The planetary mortar mixer was stirred at 125 rpm for 45 seconds to obtain an active dispersion.

[0036] Maintain the planetary mortar mixer speed at 125 rpm, and pour the premixed dry powder into the active dispersion at a uniform speed. After the premixed dry powder is poured in, maintain the planetary mortar mixer speed at 125 rpm and continue stirring for 1.5 minutes to obtain the primary slurry.

[0037] 0.07 kg of liquid sodium silicate (on a dry weight basis) was completely dissolved in 9.2 kg of the second batch of mixing water to obtain sodium silicate replenishment solution;

[0038] Reduce the speed of the planetary mortar mixer to 40 rpm, and add 100 kg of dry construction waste crushed and screened material and sodium silicate replenishment solution to the primary slurry at the same speed. After the dry construction waste crushed and screened material and sodium silicate replenishment solution are added, maintain the speed of the planetary mortar mixer at 40 rpm and mix for 2.5 minutes to obtain 3D printing mortar.

[0039] 3D printing mortar is loaded into a 3D printing machine and extruded using a high-shear pump. The extruded 3D printing mortar is then stacked layer by layer to form a 3D printed component, which is then cured under constant temperature and humidity.

[0040] Example 2:

[0041] This embodiment provides a method for preparing 3D printing mortar, including the following steps:

[0042] 45 kg of mineral powder, 15 kg of fly ash, 28 kg of fluorogypsum, 12 kg of rapid-hardening cement, 0.12 kg of fiber, 0.08 kg of sodium gluconate, 0.05 kg of borax decahydrate and 1.5 kg of sodium bentonite were put into a dry powder mixer. The dry powder mixer was controlled to mix, and the speed of the dry powder mixer was controlled to 60 rpm for 2 minutes to obtain premixed dry powder.

[0043] 18.2 kg of the first batch of mixing water was injected into the planetary mortar mixer. 0.35 kg of polycarboxylate superplasticizer and 0.15 kg of sodium hexametaphosphate were added to the first batch of mixing water. The planetary mortar mixer was stirred at 150 rpm for 60 seconds to obtain an active dispersion.

[0044] Maintain the planetary mortar mixer speed at 150 rpm, and pour the premixed dry powder into the active dispersion at a uniform speed. After the premixed dry powder is poured in, maintain the planetary mortar mixer speed at 150 rpm and continue stirring for 2 minutes to obtain the primary slurry.

[0045] 0.10 kg of liquid sodium silicate (on a dry weight basis) was completely dissolved in 9.8 kg of the second batch of mixing water to obtain sodium silicate replenishment solution;

[0046] Reduce the speed of the planetary mortar mixer to 50 rpm, and add 120 kg of dry construction waste crushed and screened material and sodium silicate replenishment solution to the primary slurry at the same speed. After the dry construction waste crushed and screened material and sodium silicate replenishment solution are added, maintain the speed of the planetary mortar mixer at 50 rpm and stir for 3 minutes to obtain 3D printing mortar.

[0047] 3D printing mortar is loaded into a 3D printing machine and extruded using a high-shear pump. The extruded 3D printing mortar is then stacked layer by layer to form a 3D printed component, which is then cured under constant temperature and humidity.

[0048] Example 3:

[0049] This embodiment provides a method for preparing 3D printing mortar, including the following steps:

[0050] Add 65kg of mineral powder, 17kg of fly ash, 15kg of fluorogypsum, 3kg of rapid-hardening cement, 0.03kg of fiber, 0.02kg of sodium gluconate, 0.02kg of borax decahydrate and 0.5kg of sodium bentonite into a dry powder mixer, control the dry powder mixer to mix, control the dry powder mixer speed to 40rpm and mix for 1min to obtain premixed dry powder;

[0051] 9.9 kg of the first batch of mixing water was injected into the planetary mortar mixer. 0.10 kg of polycarboxylate superplasticizer and 0.05 kg of sodium hexametaphosphate were added to the first batch of mixing water. The planetary mortar mixer was stirred at 100 rpm for 30 seconds to obtain an active dispersion.

[0052] Maintain the planetary mortar mixer speed at 100 rpm, and pour the premixed dry powder into the active dispersion at a uniform speed. After the premixed dry powder is poured in, maintain the planetary mortar mixer speed at 100 rpm and continue stirring for 1 minute to obtain the primary slurry.

[0053] 0.05 kg of liquid sodium silicate (on a dry weight basis) was completely dissolved in 8.1 kg of the second batch of mixing water to obtain sodium silicate replenishment solution;

[0054] Reduce the speed of the planetary mortar mixer to 30 rpm, and add 80 kg of dry construction waste crushed and screened material and sodium silicate replenishment solution to the primary slurry at the same speed. After the dry construction waste crushed and screened material and sodium silicate replenishment solution are added, maintain the speed of the planetary mortar mixer at 30 rpm and stir for 2 minutes to obtain 3D printing mortar.

[0055] 3D printing mortar is loaded into a 3D printing machine and extruded using a high-shear pump. The extruded 3D printing mortar is then stacked layer by layer to form a 3D printed component, which is then cured under constant temperature and humidity.

[0056] Comparative Examples 1-5:

[0057] Comparative Example 1:

[0058] Compared with Example 1, the difference is that sodium gluconate, borax decahydrate, sodium bentonite, sodium hexametaphosphate and liquid sodium silicate were not added, but all other ingredients were the same.

[0059] Comparative Example 2:

[0060] The difference from Example 1 is that liquid sodium silicate was not added; otherwise, they are the same.

[0061] Comparative Example 3:

[0062] Compared to Example 1, the difference is that borax decahydrate and sodium bentonite were not added, but everything else is the same.

[0063] Comparative Example 4:

[0064] Compared with Example 1, the difference lies in the timing of the preparation steps: the premixed dry powder, all the mixing water, polycarboxylate superplasticizer, sodium hexametaphosphate, liquid sodium silicate, and dry crushed and screened construction waste in the formula are put into a planetary mortar mixer at one time and mixed directly to obtain 3D printing mortar. All other steps are the same.

[0065] Comparative Example 5:

[0066] Compared with Example 1, the difference is that sodium gluconate, borax decahydrate, sodium bentonite, sodium hexametaphosphate and liquid sodium silicate were not added, and were replaced with an equal weight of conventional polymeric water-retaining thickener (hydroxypropyl methylcellulose), otherwise they are the same.

[0067] Test Examples 1-6:

[0068] Test Example 1:

[0069] The 3D printing mortar prepared in Example 1 and Comparative Example 5 were used as test samples.

[0070] The 3D printing slurry was loaded into the parallel plate testing system of the rotational rheometer, the test temperature was set to 20℃, the gap between the parallel plates was adjusted to 2.0mm, and the overflowing 3D printing slurry at the edge was scraped off.

[0071] Apply 3D printing mortar for 100 seconds -1 The shear rate was maintained for 30 seconds, followed by a 60-second rest period to eliminate the stress history generated during sample loading.

[0072] Start the three-stage step shear test program:

[0073] The first stage sets the shear rate to 0.1 s. -1 Run for 60 seconds; in the second stage, change the shear rate to 100 seconds. -1 The process runs for 60 seconds; in the third stage, the shear rate is restored to 0.1 seconds. -1 Run for 60 seconds.

[0074] Record the data points showing the change in apparent viscosity of the 3D printed mortar over time throughout the entire testing process, export the data, and plot the rheological spectrum.

[0075] Table 1. Data from the Three-Segment Step Shear Test

[0076] Testing phase Running time (s) <![CDATA[Shear rate (s -1) > Example 1 Apparent viscosity (Pa·s) Comparative Example 5: Apparent viscosity (Pa·s) Phase 1 11.5 0.1 148.23 87.41 Phase 1 47.2 0.1 153.87 91.15 Phase Two 73.8 100 2.14 18.63 Phase Two 104.1 100 1.89 17.52 Phase Three 136.5 0.1 487.56 94.34 Phase Three 168.9 0.1 512.42 97.27

[0077] The test results are as follows:

[0078] According to the data in Table 1, the 3D printing mortar prepared in Example 1 maintains a stable apparent viscosity under the first stage of low shear rate conditions, exhibiting a flow state suitable for pipeline pumping. After entering the second stage of high shear rate range, the apparent viscosity of Example 1 decreases to about 2 Pa·s.

[0079] The data change corresponds to the disintegration of the cardboard house structure formed by sodium-based bentonite under mechanical shear force, and the tearing of the in-situ generated sodium silicate and sodium hexametaphosphate cross-linked film. When the test procedure entered the third stage and returned to the initial low shear rate, the apparent viscosity of Example 1 climbed to over 500 Pa·s, exceeding the apparent viscosity value of the first stage.

[0080] The improved data indicates that the free water released after the cross-linked membrane ruptures is absorbed by the dried construction waste crushed and screened material, while the released chemicals stimulate the setting reaction of the rapid-hardening cement, enabling the 3D printing mortar to have the yield stress required for extrusion molding.

[0081] In contrast, in Comparative Example 5, where conventional hydroxypropyl methylcellulose was used to replace the rheology modulator, its apparent viscosity only recovered to a value close to that of the first stage in the third stage. This indicates that hydroxypropyl methylcellulose exhibits conventional shear-thinning properties and cannot induce a chemical-level viscosity abrupt change after undergoing high-shear exfoliation. This solution, through the combination of chemical components and the timing of preparation steps, enables the 3D printing mortar to complete its rheological transformation under shear stress changes, achieving the construction standards for printed stacking.

[0082] Test Example 2:

[0083] The primary slurry prepared in Example 1 and the 3D printing mortar extruded by high shear pump in Example 1 were used as test samples.

[0084] Weigh 5.0g of the primary slurry sample and the 3D printed mortar sample respectively, put them into glass ampoules, seal them, and place them in the test channel of the isothermal calorimeter.

[0085] The ambient temperature of the isothermal calorimeter was set to 20℃. Data points of the hydration heat release rate of the two groups of samples were recorded from 0 to 60 minutes. The data were then exported and compared.

[0086] At an ambient temperature of 20℃, primary slurry samples and 3D printed mortar samples were left to age for 30 minutes.

[0087] The primary slurry sample that has reached 30 min of age and the 3D printing mortar sample were immersed in anhydrous ethanol to terminate the hydration reaction, filtered, and then dried in a vacuum drying oven at 40℃ for 24 h.

[0088] The dried primary slurry sample and the 3D printing mortar sample were ground separately until they passed through a 200-mesh sieve. The ground powder was then placed into the sample holder of an X-ray diffractometer for scanning and testing.

[0089] The X-ray diffractometer was set to a scanning angle range of 5° to 60° and a scanning step size of 0.02° to obtain X-ray diffraction patterns at different diffraction angles.

[0090] Table 2. Test data on hydration heat release rate

[0091] Test time (min) Example 1: Primary slurry hydration heat release rate (mW / g) Example 1: Hydration exothermic rate of 3D printing slurry after extrusion (mW / g) 10 0.17 2.11 20 0.22 4.38 30 0.18 3.92 40 0.25 1.84 50 0.14 0.77 60 0.19 0.45

[0092] The test results are as follows:

[0093] Figure 1 In the figure, the horizontal axis represents the diffraction angle 2θ, in degrees; the vertical axis represents the diffraction intensity, in au. Figure 1 The solid line represents the data on the X-ray diffraction intensity of the primary slurry test object in Example 1 as a function of the diffraction angle, and the dashed line represents the data on the X-ray diffraction intensity of the 3D printed mortar test object after extrusion in Example 1 as a function of the diffraction angle.

[0094] Based on the data in Table 2 and Figure 1 As can be seen from the content, the hydration heat release rate of the primary slurry prepared in Example 1 remained below 0.3 mW / g during the test period from 0 to 60 min. The low hydration heat release rate indicates that sodium hexametaphosphate and sodium gluconate chelated the calcium and aluminum ions dissolved from the rapid-hardening cement and fluorogypsum during the primary slurry preparation stage, delaying the hydration reaction process and keeping the primary slurry in an unset state.

[0095] In Example 1, the hydration exothermic rate of the 3D printing mortar after high-shear pump extrusion increased to 4.38 mW / g within a test period of 10 to 30 minutes. The increase in the exothermic rate corresponds to the mechanical shear force causing the silicate and phosphate cross-linked film inside the 3D printing mortar to rupture, releasing the originally encapsulated chemical substances and stimulating the rapid-hardening cement and fluorogypsum to produce an exothermic hydration reaction.

[0096] Observation of the X-ray diffraction pattern revealed that the primary slurry prepared in Example 1 did not produce a diffraction peak at a diffraction angle of 2θ = 9.1°. The 3D printing mortar extruded by high-shear pump in Example 1 showed a characteristic diffraction peak representing the ettringite phase at a diffraction angle of 2θ = 9.1°.

[0097] Based on the hydration exothermic rate data, the formation reaction of ettringite crystals was inhibited in the initial slurry stage. After the extrusion process, ettringite crystals were formed in the 3D printing mortar within 30 minutes. The generated ettringite crystals provided the yield stress required for the 3D printing mortar to form, meeting the construction requirements of layer-by-layer stacking of 3D printed components without collapse.

[0098] Test Example 3:

[0099] The primary slurry prepared in Example 1 and the 3D printing mortar prepared after mixing in Example 1 were used as test samples.

[0100] The weighed primary slurry sample and the 3D printing mortar sample were respectively immersed in anhydrous ethanol for 24 hours to terminate the hydration reaction.

[0101] After removing anhydrous ethanol by filtration, the primary slurry sample and the 3D printing mortar sample were transferred to a 40℃ vacuum drying oven and dried for 48 hours.

[0102] Take out the dried primary slurry sample and the 3D printing mortar sample, and grind them separately using an agate mortar until they pass through a standard sieve with a 200-mesh aperture.

[0103] Weigh out 1.5 mg of the ground primary slurry sample powder and 3D printing mortar sample powder respectively, and mix them with 150 mg of dry potassium bromide powder.

[0104] The mixed powder is loaded into a tableting mold and pressed into a transparent sheet under a pressure of 10 MPa for 1 minute.

[0105] The pressed transparent sheet was placed in the sample chamber of the Fourier transform infrared spectrometer.

[0106] Set the spectral scanning range to 400 cm⁻¹ -1 Up to 4000cm -1 The resolution is 4cm. -1 The sample was scanned 32 times, and the transmittance data was recorded.

[0107] Table 3. Test data of characteristic absorption peak transmittance at specific wavenumbers

[0108] <![CDATA[Wavenumber (cm -1 )]]> Example 1: Primary slurry transmittance (%) Transmittance (%) of 3D printing mortar prepared in Example 1 3421.5 81.23 79.46 1643.8 88.15 86.92 1122.4 85.34 84.11 1046.2 72.87 51.34 995.7 54.62 68.21

[0109] The test results are as follows:

[0110] Figure 2 In the figure, the horizontal axis represents the wave number, with the unit being cm. -1 The vertical axis represents transmittance, in units of %. Figure 2The solid line represents the data on the transmittance of the primary slurry test object in Example 1 as a function of wavenumber, and the dashed line represents the data on the transmittance of the 3D printed mortar test object prepared in Example 1 as a function of wavenumber.

[0111] Based on the data in Table 3 and Figure 2 From the content, it can be seen that the primary slurry prepared in Example 1 has a wavenumber of 995.7 cm⁻¹. -1 An infrared absorption peak is present at the location, corresponding to a transmittance of 54.62%, at a wavenumber of 1046.2 cm⁻¹. -1 The transmittance at that point was 72.87%. The 3D printing slurry prepared by adding sodium silicate replenishment solution in Example 1 had a wavenumber of 1046.2 cm⁻¹. -1 The transmittance at that location decreased to 51.34%, and at 1000cm... -1 Up to 1100cm -1 The absorption peaks in the wavenumber range broadened.

[0112] Wavenumber 1046.2cm -1 The position corresponds to the characteristic peak of the stretching vibration of the Si-OP bridging bond. The shift and broadening of the absorption peak position, as well as the decrease in transmittance, indicate that silicate ions and phosphate ions dissociated from sodium hexametaphosphate underwent a condensation reaction. After sodium silicate in the liquid phase enters the primary slurry, it utilizes the silicate network it provides to combine with existing phosphorus-containing groups, generating a three-dimensional network of silica-phosphate crosslinked polymers.

[0113] The generated cross-linked polymer coats the surface of the dried construction waste crushed and screened material, forming an insulating film. This insulating film blocks the channels for free moisture from the surrounding environment to penetrate into the internal pores of the dried aggregate. The evolution of Si-OP characteristic groups in infrared spectroscopy confirms that the construction of the transient cross-linked network was completed by the coordination of multiple chemical components during the mixing and stirring stage.

[0114] Test Example 4:

[0115] The 3D printing mortar prepared in Examples 1 to 3 and Comparative Examples 1 to 5 were used as test samples.

[0116] According to the test standard for truncated cone molds, each group of 3D printing slurry was filled into a cone mold, the mold was lifted vertically upwards, and the diameters in two mutually perpendicular directions were measured after the slurry stopped flowing. The average value was taken as the initial flowability value.

[0117] The remaining 3D printing mortar in each group was left to stand in an environment of 20°C for 45 minutes. Its flowability was measured again using a truncated cone mold and used as the flowability value after standing for 45 minutes.

[0118] Each group of prepared 3D printing mortar was loaded into a simulated pipeline pumping device equipped with a pressure monitoring device. A constant pumping rate was set for continuous extrusion. The time from the start of pumping to the point where the pipeline pressure exceeded the safety threshold and caused the machine to stop was recorded as the maximum continuous pumping time.

[0119] The 3D printing slurries prepared in Example 1 and Comparative Example 4 were individually placed into a constant temperature test mold. Ultrasonic transmitting and receiving probes were attached to both sides of the mold. The test frequency was set to 50kHz. The pulse wave velocity data of ultrasonic waves propagating inside the slurry was continuously monitored and recorded from 0 to 60 minutes. The data was exported to generate an evolution spectrum.

[0120] Table 4. Test data on the workability and pumping stability of 3D printing mortar

[0121] Test group Initial flowability (mm) Flowability (mm) after standing for 45 minutes Maximum continuous pumping time (min) Example 1 174.5 168.2 124.3 Example 2 189.1 181.7 142.6 Example 3 152.8 147.3 98.1 Comparative Example 1 83.4 0.0 2.5 Comparative Example 2 162.7 104.5 23.8 Comparative Example 3 171.2 122.9 41.2 Comparative Example 4 91.6 0.0 4.7 Comparative Example 5 148.3 131.6 56.4

[0122] The test results are as follows:

[0123] Figure 3 In the graph, the horizontal axis represents time in minutes (min), and the vertical axis represents the ultrasonic pulse velocity in m / s. Figure 3 The solid line represents the data of the ultrasonic pulse velocity of the test object in Example 1 changing with time, and the dashed line represents the data of the ultrasonic pulse velocity of the test object in Comparative Example 4 changing with time.

[0124] Based on the data in Table 4 and Figure 3 The contents show that the initial flowability of Examples 1 to 3 is in the range of 152.8 mm to 189.1 mm, the flowability reduction after standing for 45 min is less than 10 mm, and the maximum continuous pumping time is more than 98.1 min.

[0125] This performance stems from the cross-linking reaction between sodium hexametaphosphate and liquid sodium silicate during the preparation process. The resulting cross-linked product coats the outer layer of the crushed and screened construction waste. This coating blocks the path for the porous aggregate to absorb the surrounding mixing water, ensuring sufficient free water inside the slurry for lubrication, thereby maintaining the long-term flow and pumping stability of the 3D printing mortar.

[0126] Through observation Figure 3 The ultrasonic pulse velocity in Example 1 increased gradually over 60 minutes, indicating that no large amount of water migrated into the aggregate pores or early cement hydration hardening occurred within the slurry. In Comparative Example 4, all materials were mixed at once, disrupting the sequential preparation order of complexation and crosslinking; its ultrasonic pulse velocity showed a steep increase in the initial stage of the test.

[0127] The maximum continuous pumping time of Comparative Example 4 in Table 4 is only 4.7 min, which proves that the disordered mixing sequence prevents the chemical components from playing their role in isolation and sealing in sequence. The dried aggregate absorbs the free water, causing the mortar to lose its fluidity and causing pipe blockage.

[0128] Compared to other comparative examples, Comparative Example 1, lacking rheology modifiers, resulted in porous aggregates absorbing water immediately upon contact, leading to an initial flowability of only 83.4 mm and causing pipeline blockage within 2.5 minutes. Comparative Example 2, lacking liquid sodium silicate, failed to achieve cross-linking and sealing, reducing its maximum continuous pumping time to 23.8 minutes. Comparative Example 5, using the traditional water-retaining and thickening material hydroxypropyl methylcellulose, achieved a maximum continuous pumping time of 56.4 minutes.

[0129] Traditional thickening materials rely on increasing the viscosity of the liquid phase to retain water. However, when faced with a large proportion of completely dry, porous construction waste aggregates, they cannot seal the capillary pores on the aggregate surface like an in-situ cross-linked film. Moisture will still be absorbed by the aggregate over time, leading to pipe blockage. The 3D-printed mortar prepared in this solution meets the construction requirements of preventing aggregate water absorption and maintaining long-term pumpability.

[0130] Test Example 5:

[0131] The 3D printing mortar prepared by stirring in Examples 1 to 3, Comparative Example 3 and Comparative Example 5 was used as test samples.

[0132] Each group of 3D printing mortar was loaded into the feeding bin of the 3D printing equipment. The cross-sectional dimensions of the printing nozzle were set to a width of 30mm and a height of 15mm, and the moving speed of the printing head was set to 80mm / s.

[0133] The 3D printing equipment is controlled to perform a single-line reciprocating linear stacking operation on a horizontal substrate, with the printing length of each layer set to 500mm.

[0134] Observe the stacking process and record the number of printing layers when the edges of the bottom printed mortar lines crack or the whole becomes unstable and collapses. This number is recorded as the maximum number of consecutive stacked layers.

[0135] Stop printing just before the bottom line collapses, use calipers to measure the center height of the bottom printed line, calculate the percentage difference between the center height and the nozzle height of 15mm, and record it as the bottom height deformation rate.

[0136] Separate 3D printed mortar samples from Example 1 and Comparative Example 5 after extrusion through the printing nozzle were loaded into the detection tube of a low-field nuclear magnetic resonance analyzer.

[0137] The test temperature of the low-field nuclear magnetic resonance analyzer was set to 20℃, and the proton spin echo attenuation signal inside the 3D printed mortar was acquired using the CPMG pulse sequence.

[0138] Export the collected signal data and perform data inversion processing to obtain the transverse relaxation time distribution spectrum of the test sample.

[0139] Table 5. 3D Printing Construction Performance Test Data

[0140] Example 1 48 2.1 Example 2 52 1.8 Example 3 41 3.5 Comparative Example 3 12 18.6 Comparative Example 5 16 14.3

[0141] The test results are as follows:

[0142] Figure 4 In the graph, the horizontal axis represents the horizontal relaxation time in milliseconds (ms), and the vertical axis represents the signal amplitude in au (au). Figure 4 The solid line represents the data of the signal amplitude of the test object in Example 1 changing with the transverse relaxation time, and the dashed line represents the data of the signal amplitude of the test object in Comparative Example 5 changing with the transverse relaxation time.

[0143] Based on the data in Table 5 and Figure 4 The data shows that the maximum number of consecutive stacked layers in Examples 1 to 3 all exceeded 40 layers, and the deformation rate of the bottom layer was in the relatively low range of 1.8% to 3.5%. After extrusion and stacking, the bottom layer of the 3D printing mortar bears the gravitational load accumulated by the upper material. The low deformation rate indicates that yield stress resisting external deformation has been generated inside the mortar. This construction performance data comes from the change in state of the preparation components after pumping and shearing.

[0144] observe Figure 4 The transverse relaxation time distribution spectrum reflects the binding state of water molecules within the material. Transverse relaxation times in the range of 0.1 ms to 10 ms represent bound water adsorbed by solid particles, while those in the range of 10 ms to 1000 ms represent free water within the pores. In Example 1, the signal amplitude of the test object in the 10 ms to 1000 ms range was lower than that of the test object in Comparative Example 5, while the signal amplitude in the 0.1 ms to 10 ms range was at a higher level.

[0145] The difference in signal amplitude distribution illustrates that in Example 1, after the extrusion operation, the original cross-linked sealing membrane disintegrates, and the isolated free water comes into contact with and is adsorbed by the crushed and screened construction waste. The free water is transformed into bound water and the bound water required for the hydration reaction. This change in water state causes the 3D printing mortar to lose its fluidity and form a plastic state with supporting and load-bearing capacity.

[0146] Comparative Example 3 lacked some crosslinking components, while Comparative Example 5 used hydroxypropyl methylcellulose as a substitute component. Neither of these alternative schemes established a crosslinking blocking and shear breakage mechanism, and free water that provides lubrication was still retained after the extrusion operation.

[0147] In Table 5, the maximum number of consecutive stacked layers in Comparative Examples 3 and 5 is less than 20, and the deformation rate of the bottom layer exceeds 14%, indicating that the test objects did not generate yield stress to resist gravity after extrusion, resulting in rheological collapse. The test results confirm that the implementation scheme achieved the required stacking construction performance for 3D printing by controlling the moisture distribution.

[0148] Test Example 6:

[0149] The 3D printed components of Examples 1 to 3 and Comparative Example 5, after being extruded and stacked by a 3D printing equipment and cured for 24 hours, were used as test samples.

[0150] The 3D printed component was cut into standard-sized test blocks of 40mm × 40mm × 160mm using a rock cutter.

[0151] The cut standard-sized test blocks were transferred into a constant temperature and humidity curing chamber with a temperature of 20℃ and a relative humidity of 95%, and cured for 1 day, 7 days and 28 days respectively.

[0152] Once the test block reaches the corresponding age, remove the standard-sized test block, wipe off the surface moisture, and place the standard-sized test block on the flexural fixture of the computer-controlled electronic universal testing machine.

[0153] Start the testing machine to perform a three-point flexural load test on the standard-sized specimen, record the failure load data at the moment of specimen breakage, and calculate and record the corresponding flexural strength.

[0154] Collect standard-sized specimen fragments after flexural strength test fracture, place them at the center of the compression fixture, set the loading rate to 2.4 kN / s for compression test, record the failure load data when the specimen is crushed, and calculate and record the corresponding compressive strength.

[0155] Standard-sized specimens from Example 1 and Comparative Example 5, cured to 28 days of age, were selected separately and subjected to uniaxial constant strain rate compression loading using an electro-hydraulic servo rock mechanics testing machine. Stress and strain data points were collected throughout the entire process of compression failure, and the data were exported to generate stress-strain maps.

[0156] Table 6. Test data of mechanical properties of 3D printing mortar at different ages

[0157] Test group 1-day compressive strength (MPa) 7-day compressive strength (MPa) 28-day compressive strength (MPa) 1-day flexural strength (MPa) 7-day flexural strength (MPa) 28-day flexural strength (MPa) Example 1 15.24 28.47 42.13 3.51 6.22 8.46 Example 2 17.18 31.54 45.81 3.94 6.87 8.93 Example 3 12.86 25.92 38.65 3.12 5.75 7.62 Comparative Example 5 8.41 17.26 24.58 2.15 3.84 4.97

[0158] The test results are as follows:

[0159] Figure 5 In the figure, the horizontal axis represents strain, and the vertical axis represents stress, with the unit being MPa. Figure 5 The solid line represents the stress-strain variation data of the test object in Example 1, and the dashed line represents the stress-strain variation data of the test object in Comparative Example 5.

[0160] Based on the data in Table 6 and Figure 5 The results show that the compressive and flexural strengths of Examples 1 to 3 at all ages exceeded those recorded in Comparative Example 5. The 28-day compressive strength of the test subject in Example 1 reached 42.13 MPa.

[0161] from Figure 5 Observing the curve trend, the upward slope of the curve in Example 1 is larger, the peak stress point is located higher, and the area enclosed by the curve and the horizontal axis is larger than that in Comparative Example 5. This indicates that Example 1 has the stiffness to resist external loads and can withstand more deformation energy.

[0162] The strength data is derived from the controlled chemical reaction sequence during the preparation process. Sodium gluconate and borax decahydrate suppress the exothermic hydration process of rapid-hardening cement in the primary slurry stage. After the slurry is extruded through the printing equipment, the previously formed silicate and phosphate cross-linked film breaks down, releasing the isolated mixing water and active ions.

[0163] This delayed triggering mechanism allows the hydration reaction to occur concentratedly after the 3D printed component has solidified. The generated hydrated calcium silicate gel and ettringite crystals interweave and coexist in the pores of the crushed and screened construction waste. Residual cross-linked film fragments further combine with free calcium ions, filling the voids at the interface between the slurry and the solid aggregate.

[0164] Comparative Example 5 used conventional hydroxypropyl methylcellulose to replace the reaction components, and no encapsulation delay mechanism was formed within the slurry. Some hydration reactions occurred prematurely during the stirring and pumping stages, resulting in the extruded product failing to construct a dense, continuous hydration network. Free water uncontrollably penetrated into the porous aggregate, causing a loose structure after hardening. The compressive strength data of the test objects demonstrate that the chemical crosslinking and desealing process designed in this scheme ensures the load-bearing performance of the final component.

Claims

1. A method for preparing 3D printing mortar, characterized in that, Includes the following steps: Mineral powder, fly ash, fluorogypsum, rapid-hardening cement, fiber, sodium gluconate, borax decahydrate, and sodium bentonite are added to a dry powder mixer, and the dry powder mixer is controlled to mix them to obtain premixed dry powder. The first part of the mixing water is injected into the planetary mortar mixer. Polycarboxylate superplasticizer and sodium hexametaphosphate are added to the first part of the mixing water. The speed of the planetary mortar mixer is controlled to stir, and an active dispersion is obtained. Maintaining the rotation speed of the planetary mortar mixer, the premixed dry powder is poured into the active dispersion at a uniform speed, and the mixture is continuously stirred to obtain a primary slurry. The liquid sodium silicate is completely dissolved in the second batch of mixing water to obtain the sodium silicate replenishment solution; The rotation speed of the planetary mortar mixer is lower than that of the preparation process. The dried crushed and screened construction waste and the sodium silicate replenishment solution are added to the primary slurry at the same speed. After the addition is completed, the rotation speed of the planetary mortar mixer is maintained to stir, thereby obtaining 3D printing mortar.

2. The preparation method according to claim 1, characterized in that, The weight proportions of each raw material added to the dry powder mixer are as follows: The composition includes 45-65 parts of mineral powder, 15-20 parts of fly ash, 15-28 parts of fluorogypsum, 3-12 parts of rapid-hardening cement, 0.03-0.12 parts of fiber, 0.02-0.08 parts of sodium gluconate, 0.02-0.05 parts of borax decahydrate, and 0.5-1.5 parts of sodium-based bentonite.

3. The preparation method according to claim 2, characterized in that, The weight proportions of the first part (mixing water), polycarboxylate superplasticizer, sodium hexametaphosphate, liquid sodium silicate, the second part (mixing water), and dried construction waste crushed and screened material are as follows: The first part consists of 9.9-18.2 parts of mixing water, 0.10-0.35 parts of the polycarboxylate superplasticizer, 0.05-0.15 parts of the sodium hexametaphosphate, 0.05-0.10 parts of the liquid sodium silicate by dry weight, 8.1-9.8 parts of mixing water in the second part, and 80-120 parts of the dried construction waste crushed and screened material.

4. The preparation method according to claim 1, characterized in that, The specific operating conditions for controlling the mixing of the dry powder mixer are as follows: The dry powder mixer speed is controlled at 40-60 rpm, and the mixing time is 1-2 min.

5. The preparation method according to claim 1, characterized in that, The specific operating conditions for controlling the rotation speed of the planetary mortar mixer are as follows: The speed of the planetary mortar mixer is controlled at 100-150 rpm, and the mixing time is 30-60 seconds.

6. The preparation method according to claim 5, characterized in that, After the premixed dry powder is poured in, the operating conditions for continuous stirring are as follows: Maintain the planetary mortar mixer speed at 100-150 rpm and continue mixing for 1-2 minutes.

7. The preparation method according to claim 1, characterized in that, The specific operating conditions for maintaining the planetary mortar mixer speed at a speed lower than that for the preparation of the primary slurry are as follows: Dry crushed and screened construction waste material and the sodium silicate supplement solution are added synchronously and uniformly to the primary slurry. The planetary mortar mixer operates at a speed of 30-50 rpm. After the dried construction waste crushed and screened material and the sodium silicate replenishment solution are added, the planetary mortar mixer is maintained at a speed of 30-50 rpm for 2-3 minutes.

8. The preparation method according to claim 3, characterized in that, The total weight parts of all raw materials used in preparing the 3D printing mortar are limited to: The composition includes 55 parts of mineral powder, 20 parts of fly ash, 20 parts of fluorogypsum, 5 parts of rapid-hardening cement, 0.07 parts of fiber, 0.05 parts of sodium gluconate, 0.03 parts of borax decahydrate, 1.0 part of sodium bentonite, 13.8 parts of the first batch of mixing water, 0.20 parts of polycarboxylate superplasticizer, 0.10 parts of sodium hexametaphosphate, 0.07 parts of liquid sodium silicate (dry weight), 9.2 parts of the second batch of mixing water, and 100 parts of the dried construction waste crushed and screened material.

9. The preparation method according to claim 3, characterized in that, The total weight parts of all raw materials used in preparing the 3D printing mortar are limited to: The composition includes 45 parts of mineral powder, 15 parts of fly ash, 28 parts of fluorogypsum, 12 parts of rapid-hardening cement, 0.12 parts of fiber, 0.08 parts of sodium gluconate, 0.05 parts of borax decahydrate, 1.5 parts of sodium bentonite, 18.2 parts of the first batch of mixing water, 0.35 parts of polycarboxylate superplasticizer, 0.15 parts of sodium hexametaphosphate, 0.10 parts of liquid sodium silicate (dry weight), 9.8 parts of the second batch of mixing water, and 120 parts of dried construction waste crushed and screened material.

10. The preparation method according to claim 3, characterized in that, The total weight parts of all raw materials used in preparing the 3D printing mortar are limited to: The composition includes 65 parts of mineral powder, 17 parts of fly ash, 15 parts of fluorogypsum, 3 parts of rapid-hardening cement, 0.03 parts of fiber, 0.02 parts of sodium gluconate, 0.02 parts of borax decahydrate, 0.5 parts of sodium bentonite, 9.9 parts of the first batch of mixing water, 0.10 parts of polycarboxylate superplasticizer, 0.05 parts of sodium hexametaphosphate, 0.05 parts of liquid sodium silicate (dry weight), 8.1 parts of the second batch of mixing water, and 80 parts of the dried construction waste crushed and screened material.